Digital Game in Enhancing Pupils’ English Vocabulary in Islamic Elementary School - Itami Idrus, Andi Yuni; Asmid, Masruddin; Jufriadi (Institut Agama Islam Negeri Palopo, 2024)
This thesis discusses increasing English vocabulary through digital games on the Wordwall application for students at Al-Hikmah Islamic Elementary School, Palopo City. This research aims to determine students' ability to improve their vocabulary using digital games on the Wordwall application. Classroom action research (CAR) is the term for this type of research. This research consists of 2 cycles, where there were four stages, namely; planning, implementation, observation and reflection. The subjects of this research were 22 class 5.B students. The results of the research showed that there was an increase in students' vocabulary skills from cycle 1 to cycle 2. In cycle 1 it was stated that there had not been a significant increase because there were results where 13 students in the undeveloped category or (59%), 9 students in the category had started developing or (41%), and 0 students were included in the category developing as expected or in the category developing very well. In Cycle 2, the increase in students' English vocabulary skills through digital games on the Wordwall application experienced an increase where there were 0 students who were in the undeveloped category or (0%), 4 students were in the starting to develop category or (15%), 12 students were in the category developing as expected or (62%), and 6 students were in the category developing very well or (23%). From the results of this data, Cycle 1 got an average score of 6 (33%) or undeveloped, while cycle 2 got an average score of 12 (67%) or developed according to expectations, which means research on improving students' English skills through digital games in Al-Hikmah Islamic Elementary School, Palopo City, was declared complete.